Performance evaluation of coated carbide cutting tools when turning hardened tool steel - Tang, Yu Cai (2006)
Hard turning is a more economical technology that is developed to substitute grinding in the finishing operations of hardened material (HRC 45 and above). However, the potential of this technology is limited due to the high cost of ceramics and cubic boron nitride (CBN) cutting inserts. In order for hard turning to be truly viable, the performance of more economical cutting tools must be justified. This research project was undertaken to investigate the performance of KC 5010 physical vapor deposition (PVD) titanium aluminium nitride (TiAlN) conventional and wiper geometry inserts during finish hard turning of Stavax Electro-Slag-Refining (ESR) stainless tool steel (HRC 47 - 48). Tool performance, tool failure modes and wear mechanisms were investigated under various cutting conditions. Machinability parameters namely tool life and surface roughness were evaluated. Response surface methodology (RSM) was used to model the relationship between the response of interest (tool life and surface roughness) and several variables (cutting speed and feed rate) for the conventional insert. It was found that flank wear near the nose in the minor flank region of the insert was the main wear form found on KC 5010 inserts as crater wear was not severe. The wear mechanisms responsible were mainly abrasion and adhesion. At high cutting speed (170 m/min), there was a strong tendency for the tools to fail catastrophically. Wiper geometry inserts were capable of producing better surface finish compared to conventional geometry inserts but with a shorter tool life for similar cutting conditions. The tool life and surface roughness models developed for conventional inserts were found to be statistically valid and adequate to predict the machining responses under certain cutting conditions. Only minimal discrepancy was found between the predicted and actual values. Based on this analysis, hard turning with coated carbide conventional and wiper geometry inserts is indeed promising.